Consistency of The Arrangements Granting Extensions of The Term of Building use Rights for Houses to Provide Legal Certainty - Putra Pangestu, Hendy; Koeswahyono, Imam; Sri Kawuryan, Endang (Universitas Muhammadiyah Malang, 2024)
There is ambiguity in the regulation for granting HGB term extensions. Article 35 of the UUPA do not recognize the granting of an extension